DISPARITY OF JUDGEMENTS TOWARD DRUG-RELATED CRIME (STUDY OF DECISION NUMBER 47/PID.SUS/2024/PN TBT AND DECISION NUMBER 48/PID.SUS/2024/PN TBT) - Marlina; Yohana Serevina Mikha Gusta; Yati Sharfina Desiandri (CV Rewang Rencang, 2024)
Narcotics crimes in Indonesia have caused many victims, especially among the young generation of the nation, which is very dangerous for the lives of society, the nation, and the state. In enforcing criminal law against narcotics crimes, it is a concern in connection with the rampant disparity in sentencing. The court decisions in Case Number 47/Pid.Sus/2024/PN.Tbt and Case Number 48/Pid.Sus/2024/PN. Tbt imposed sentences with very different differences, so that the considerations and implications need to be studied in depth. The results of this study indicate that there is no legal regulation that prohibits disparity in sentencing. The occurrence of disparity in sentencing for narcotics crimes in the verdict of narcotics crimes Case Number 47/Pid.Sus/2024/PN.Tbt and Case Number 48/Pid.Sus/2024/PN. Tbt refers to the principle of judges' freedom in carrying out their judicial functions. The judge's considerations in the verdict of narcotics crimes Case Number 47/Pid.Sus/2024/PN.Tbt with defendant Jefri and Case Number 48/Pid.Sus/2024/PN. Tbt with defendant Supriadi are an integral and inseparable unit, but there was an error in the judge's considerations so that the sentences were imposed with very different differences. The implications of the disparity in sentencing in the two decisions are that there is injustice, uncertainty and uselessness in law enforcement against narcotics crimes.